Trans and postoperative endoscopic assistance in an esophageal gastro anastomosis: case report - Trinidad-Rodríguez, Williams; Barrón-Soto, Mauricio Luis; Payán-Gómez, Mayo Alexander; Moreno-Martínez, Irán; Vidal-Santiago, Daniela (International Journal of Research in Medical Sciences, 2024)
Esophageal anastomosis leak has an average incidence of 10% and three times the risk of mortality. Use should be made of all available tools to reduce the risk of anastomotic leak. Endoscopy could be useful during the trans and postoperative period to reduce morbidity and mortality in high-risk esophageal anastomoses. We present this case as proof of this.